EL PODER PREDICTIVO EN LA PRONUNCIACION DE PALABRAS INGLESAS NOVELES POR HABLANTES BILINGÜES - Cuenca Villarín, María Heliodora (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Teaching English pronunciation should involve not only production and reception exercises but also the formation of predictive power for the pronunciation of novel words. In the analysis of the strategies followed by learners of English in the generation of phonological forms of novel words, three types of actions have been observed: a direct visual word recognition process, an activation of analogous words, and the application of graphemeto-phoneme conversion rules. The reading of a list of words and pseudowords by bilingual speakers of English and Spanish has been analyzed in order to find out to which extent their strategies are similar to those used by EFL learners. In fact, they employ identical strategies, although in different proportions highly correlated with their amount of experience in the language under study: the bilingual speakers studied favored a direct visual word recognition process and the activation of analogous words in the generation of phonological forms for pseudowords.